The Pilot Study of the Influence of Free Ammonia on Membrane Fouling during the Partial Nitrosation of Pig Farm Anaerobic Digestion Liquid - Hanxiao Bian (MDPI AG, 2021)
The problem of membrane fouling is a key factor restricting the application of the membrane bioreactor (MBR) in the partial nitrosation (PN) and anaerobic ammonia oxidation (anammox) processes. In this study, the pilot-scale continuous flow MBR was used to start up the partial nitrosation process in order to investigate the change trend of mid-transmembrane pressure (TMP) in the process of start-up, which was further explored to clarify the membrane fouling mechanism in the pilot-scale reactor. The results showed that the MBR system was in a stable operating condition during the partial nitrosation operation and that the online automatic backwash operation mode is beneficial in alleviating membrane fouling and reducing the cost of membrane washing. Particular attention was paid to the influence trend of free ammonia (FA)on membrane fouling, and it was found that the increase in FA concentration plays the most critical role in membrane fouling. The increase in FA concentration led to an increase in the extracellular polymer (EPS), dissolved microorganism product (SMP) and soluble chemical oxygen demand (SCOD) concentration. FA was extremely significantly correlated with EPS and SCOD, and the FA concentration was approximately 20.7 mg/L. The SCODeff (effluent SCOD concentration) concentration was approximately 147 mg/L higher than the SCODinf (influent SCOD concentration) concentration. FA mainly affects membrane fouling by affecting the concentration of EPS and SCOD.